Factors motivating code switching within the social contact of Hausa bilinguals - Inuwa, Yusuf Nuhu; Christopher, Anne Althea; Bakrin, Haryati (2014)
The study reported in this paper centers on the factors motivating code switching within the social contact of Hausa bilingual speakers studying at University Utara Malaysia. Information for the survey was collected using questionnaire sets distributed to 80 bilinguals, who completed them.The data were examined within the sketch of Holmes (2013) social factors and social dimensions of language use.The result of the investigation established that alternating between two languages is a discourse strategy use by bilinguals to communicate effectively, which is mostly influenced by certain social variables and morphosyntactic structures of the languages.